Analisis Penetapan Ujrah dalam Akad Rahn Tasjily Perspektif Fatwa DSN-MUI No. 68/DSN-MUI/III/2008 dan Ekonomi Syariah - Moh. Asep Zakariya Ansori; Anisa Husnul Khatimah; Siti Alamatul Kamilah; Rival Alvarizi; Daffyana Eka Nugraha; Naufal Budaeri A; Dimas Adi Saputra (As-Syirkah: Islamic Economic & Financial Journal, 2026)
This study aims to analyze the mechanism for determining ujrah (rental fee) in the Rahn Tasjily contract based on the provisions of DSN-MUI Fatwa No. 68/DSN-MUI/III/2008 and the perspective of Islamic economics. The main issue examined is the practice of determining ujrah in some Islamic financial institutions, which is still linked to the amount of the loan (marhun bih), rather than being based on service benefits or actual storage costs as regulated in DSN-MUI Fatwa No. 68/DSN-MUI/III/2008, thereby potentially deviating from the principles of ijarah in Islamic economics. This study employs a qualitative method based on library research with a juridical-normative approach and content analysis. Primary data sources include DSN-MUI fatwas, PSAK (Indonesian Financial Accounting Standards), and related sharia provisions, while secondary data are obtained from academic journals, books, and relevant regulations. The findings show that: (1) DSN-MUI Fatwa No. 68/2008 explicitly prohibits determining ujrah based on the amount of the loan; (2) ujrah must be determined based on service benefits, storage costs, and actual maintenance costs, rather than the loan amount; and (3) practices that base ujrah on marhun bih contradict the principle of justice (‘adl) in Islamic economics and may contain hidden riba nasi’ah. This study strengthens the normative argument regarding the mechanism of determining ujrah in accordance with DSN-MUI Fatwa and Islamic economic principles as a reference for Islamic financial institutions.